The economic and legal identity of the self-employed in Anglo-Australian Jurisdictions. (2nd January 2016) - Carrigan, Frank
ABSTRACT: The objective of the article is to track the part played by self-employed or independent contractors in shaping the wage contract. A petite bourgeoisie class that cannot be a party to an employment contract has been influential in shaping its judicial design. The reality is that in both English and Australian doctrine the judiciary has utilised the distinction between independent contractors and workers as the benchmark for categorising those embraced by an employment contract. The article argues that this state of affairs has resulted in a long standing judicial failure to provide a lucid exposition of the economic characteristics of the self-employed and wage earners, and that this has produced over an extensive historical period a series of misguided contract of employment tests. The failure to provide a cogent legal test for distinguishing the self-employed from those selling labour hours has a steep cost. When those who should be categorised as employees are classified as independent contractors the victims lose the prospect of access to employment protection rights. Social justice is the loser when the law fails to adopt a test that accurately identifies those asserting their right to the protective mantle of labour laws. A cardinal feature of the article is the space given to revisionist judges who in the past have been willing to take tentative steps towards forging an employment contract test that better reflected the economic lines separating the self-employed or independent contractors from wage labour. These bold spirits have been prepared to take the bull by the horns and begin the process of seeing class as an organising principle in distinguishing employees from independent contractors.